2014
DOI: 10.15666/aeer/1204_931946
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Austrian pine on naturalness and succession of vegetation in reclaimed bauxite quarries

Abstract: Phytosociological and nature conservation assessment of the herb layer of 6-, 15-and 20-yearold post-mining Austrian pine stands was conducted in reclaimed bauxite quarries in Hungary. Great differences among the vegetations were found. Disturbance-tolerant species were dominant, subdominant and subordinated in the youngest, middle-aged and oldest pine stand, respectively. In parallel, proportion of the species characteristic for natural habitats increased gradually, leading to growing diversity and naturalnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…The flora of habitats subjected to the highest level of anthropogenic impact had a high proportion of annual species, but not the highest proportion of non-native species (Kim et al, 2002). The naturalness of the plant community increases during restoration succession at the reclamation site, which was confirmed using the quasi-mean naturalness value (Cseresnyés et al, 2014). Our results suggest that as the community approaches the middle part of the hemeroby/naturalness gradient, the number of possible community states increases, so diversity of the community in the middle part of the disturbance gradient is the greatest.…”
Section: Discussionsupporting
confidence: 73%
“…The flora of habitats subjected to the highest level of anthropogenic impact had a high proportion of annual species, but not the highest proportion of non-native species (Kim et al, 2002). The naturalness of the plant community increases during restoration succession at the reclamation site, which was confirmed using the quasi-mean naturalness value (Cseresnyés et al, 2014). Our results suggest that as the community approaches the middle part of the hemeroby/naturalness gradient, the number of possible community states increases, so diversity of the community in the middle part of the disturbance gradient is the greatest.…”
Section: Discussionsupporting
confidence: 73%
“…Lenda et al ; Prach et al ; Tischew et al ; Heneberg & Řezáč ) as shown by the occurrence of rare and even threatened species of plants and various groups of insects (Novák & Prach ; Heneberg et al ; Řehounková et al ). This value, however, largely depends on the restoration method applied, that is, spontaneous revegetation or forestry reclamation (Tropek et al ; Ballesteros et al ; Řehounková et al ; Šebelíková et al ), the latter being usually applied in most of Europe (Badía et al ; Pietrzykowski & Socha ; Krümmelbein et al ; Cseresnyés et al ). Forestry reclamation means artificial afforestation preceded by land remodeling, topsoil overlay, or fertilization (Kaźmierczak et al ) resulting prevailingly in monocultural stands arranged in dense rows (Pietrzykowski & Socha ) with more or less homogeneous site conditions (Cseresnyés et al ).…”
Section: Introductionmentioning
confidence: 99%
“…This value, however, largely depends on the restoration method applied, that is, spontaneous revegetation or forestry reclamation (Tropek et al ; Ballesteros et al ; Řehounková et al ; Šebelíková et al ), the latter being usually applied in most of Europe (Badía et al ; Pietrzykowski & Socha ; Krümmelbein et al ; Cseresnyés et al ). Forestry reclamation means artificial afforestation preceded by land remodeling, topsoil overlay, or fertilization (Kaźmierczak et al ) resulting prevailingly in monocultural stands arranged in dense rows (Pietrzykowski & Socha ) with more or less homogeneous site conditions (Cseresnyés et al ). In the Czech Republic, Pinus sylvestris (Scots pine) is the most frequent woody species planted in afforested sand and sand‐gravel pits being considered as an easy colonizer of nutrient‐poor habitats (Chytrý ; Řehounková et al ).…”
Section: Introductionmentioning
confidence: 99%